TRAPPING AND DISRUPTION OF THE MATING ACTIVITY OF SCAPANES AUSTRALIS USING LIVE MALE AS BAIT IN PAPUA NEW GUINEA - Kakul, T.K; Laup, S; Stathers, T.; Beaudoin -Ollivier, L.; Morin, J.P; Rochat, D (International Coconut Community Journal, 1999)
Scapanes australis is a major insect pest of coconut palms in Papua New Guinea. Field observations showed that on host plants like coconuts, male Scapanes always attracted females and other male members. Bucket traps were developed to lure Scapanes beetles using live males as attractant (bait). Live males feeding on sugarcane were placed singly in an inner bucket within a 10 litres bucket container with rectangular holes at the side for insect entry and soapy water inside for drowning the insects. Scapanes populations were continuously monitored by traps and results indicated a gradual decline in the Scapanes population over time. Traps were also placed in the field to see if losses to coconuts used by Scapanes can be reduced. Results indicated that the reduction in trap catches was not consistent. Further studies are required to study the physiological behavior of male Scapanes and to improve the technique of trapping of Scapanes with male member alone. The role of trapping Scapanes in pest management is discussed.